SAT0482 Role of the rheumatologist in the diagnosis and treatment of rheumatoid arthritis and quality of care from the patient perspective. (23rd January 2014) - Bolge, S.; Schenkel, B.; Lorenzo, R.; Ramesh, V.; Ingham, M.P.
Abstract : Background: Rheumatologists are critical to the appropriate diagnosis and treatment of rheumatoid arthritis (RA). EULAR recommends that early RA patients be referred to and treated by a rheumatologist within six weeks of onset of symptoms. Objectives: To detail the role of the rheumatologist in the diagnosis and treatment of RA patients and describe current quality of care from the patient perspective. Methods: Patients self-reporting a diagnosis of RA and residing in the United States completed a self-administered, internet-based questionnaire in the Fall of 2011. Patients provided details about providers who diagnosed and treated their RA. Patient satisfaction with care was defined as 5-7 (5=somewhat satisfied, 6=very satisfied, 7=extremely satisfied) on a 7-point Likert scale. Results: A total of 2138 patients (76% female, mean age 56.4) completed the questionnaire. Less than half were initially diagnosed with RA by a rheumatologist (48%); 46% were diagnosed by a primary care physician (PCP) and 6% by another specialist. Of those not initially diagnosed by a rheumatologist (n=1121), 38% were immediately referred to one and another 5% were referred within a year, but 41% were never referred to a rheumatologist. Among all patients, 27% never visited a rheumatologist. Patients who never visited a rheumatologist (n=529) reported various reasons: satisfaction with PCP (42%); physician never suggested it (35%); PCP is very knowledgeable about RA (34%); PCP is treating other conditions (28%); patient does not believe RA is severe enough (24%); nothing a rheumatologist would do differently (20%); out of pocket cost is too expensive (19%). Among all patients, 56% are currently seeing a rheumatologist, and 53% report that a rheumatologist is the primary treating physician; 41% are currently seeing a PCP for RA, and 33% report a PCP is the primary treating physician. Among patients currently seeing a rheumatologist (n=1202), 86% express satisfaction with care, and most patients are satisfied that their rheumatologist: is knowledgeable about RA (93%); lets patient talk freely (90%); communicates simply/clearly (89%); gives patient full attention (89%); is someone patient can trust (89%); takes concerns seriously (88%); explains options (87%); lets patient participate in treatment decisions appropriately (87%); provides effective RA treatments (86%); encourages patient to ask questions about treatment (84%); is open-minded about new treatments (84%). Conclusions: Rheumatologists play a key role in diagnosis and treatment of RA. However, there remain many patients who continue to rely solely on PCPs and who may benefit from a collaborative approach between PCPs and rheumatologists. Patients recognize the level of knowledge provided by rheumatologists. Patients currently treated by a rheumatologist have high satisfaction rates for quality of patient-physician communications and shared decision making. References: Combe B, et al. EULAR recommendations for the management of early arthritis: report of a task force of the European Standing Committee for International Clinical Studies Including Therapeutics (ESCISIT). Ann Rheum Dis 2007;66:34–45. Disclosure of Interest: S. Bolge Employee of: Janssen Scientific Affairs, LLC, B. Schenkel Employee of: Janssen Scientific Affairs, LLC, R. Lorenzo Consultant for: Janssen Scientific Affairs, LLC, V. Ramesh Consultant for: Janssen Scientific Affairs, LLC, M. Ingham Employee of: Janssen Scientific Affairs, LLC